Applications and Outcomes of Telehealth and Integrated Care in Men’s Health Urology - Bryce Bisset; Tarun Shriram; Meenakshi Davuluri; Hassan Azar; Jonathan Beilan; Reza Amin; Justin Houman (Journal of Medical Internet Research, 2025)
AbstractMen’s health, particularly in the domain of urology, faces significant challenges in access to care, patient outcomes, and cost efficiency. Despite advances in medical treatment, conditions such as prostate cancer remain a leading cause of cancer-related death among men, with African American men disproportionately affected at twice the mortality rate of other groups. Compounding these challenges is a critical shortage of urologists, with 62% of US counties lacking a practicing urologist and only 1 new urologist entering the field for every 10 retiring. This shortage results in delayed diagnoses, increased rates of advanced-stage conditions, and significant health disparities. To address these pressing issues, telehealth and technology-based integrated care models present a promising solution. Telehealth expands access to specialized urological care by overcoming geographical barriers and offering virtual consultations, at-home diagnostics, and continuous patient engagement. Artificial intelligence–driven tools further enhance the efficiency and accuracy of care delivery, improving provider experience by automating administrative tasks and facilitating early intervention through predictive analytics. Furthermore, remote patient monitoring devices provide accurate, cost-effective, and highly accessible alternatives. These innovations reduce provider burnout, lower health care costs, and, critically, improve patient outcomes. This paper explores the potential of telehealth and integrated care in men’s health urology as a practical pathway to bridging access gaps, enhancing care quality, and achieving cost savings. By leveraging digital health solutions, health care systems and employers can promote health equity, increase engagement, and ensure that all men receive timely and effective urological care.